Song Copyright Royalties as Distribution Joint Assets in Decision No.1622/ Pdt.G /2023/PAJB Islamic Law Perspective - Moh Hosen; Adul Aziz Wahab; Yudi Arianto (Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
This study analyzes the distribution of song copyright royalties as joint property in West Jakarta Religious Court Decision No.1622/Pdt.G/2023/PAJB from the perspective of Islamic law. The research was conducted using a qualitative method involving an in-depth analysis of the court decision and a literature review on the concept of joint property and intellectual property rights in Islamic law. The results showed that song copyright royalties obtained during marriage can be categorized as joint property if both parties contribute equally in obtaining it. According to the view of Islamic law, joint property is considered to arise from the principle of cooperation between husband and wife (syirkah abdan) in earning a living to meet family needs. The division of joint property is submitted based on agreement (ash-shulh) by considering the contribution and justice for each party. The decision of the West Jakarta Religious Court has considered the rights and contributions of both parties fairly in the distribution of song copyright royalties by giving half of the share to each party. This research is useful to provide a comprehensive understanding of the status of song copyright royalties as an object of joint property and how the division can be done fairly according to the principles of Islamic law.